2017
DOI: 10.1021/acs.macromol.6b02665
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Zwitterionic Diblock Copolymers with Cleavable Biotin Groups at the Junction Points and Fabrication of Bioconjugates by Biotin–Streptavidin Coupling

Abstract: Combinations of synthetic polymers and natural proteins provide a route to the synthesis of new biomaterials. The bioconjugates combining tunable properties of polymers with functionalities of proteins have found broad applications. One of the most challenging problems in this research field is the self-assembly behaviors of responsive polymer−protein bioconjugates. In this research, synthesis and self-assembly of bioconjugates composed of zwitterionic block copolymer and streptavidin were investigated. Block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 48 publications
(69 reference statements)
1
38
0
Order By: Relevance
“…We ando ther researchers have demonstrated that the conjugation of proteins to thermally responsivep olymers could change the phase-transition temperatures of the polymers significantly. [21][22][23][24] The shift in the phasetransition temperature of PNIPAM in PPL nanogelsi sa ttributed to the incorporation of PPL molecules to the network structures and an increase in the hydrophilicity of the polymer. After coating with BSA, the endotherm of PNIPAM shifts to the high-temperature regime.…”
Section: Resultsmentioning
confidence: 99%
“…We ando ther researchers have demonstrated that the conjugation of proteins to thermally responsivep olymers could change the phase-transition temperatures of the polymers significantly. [21][22][23][24] The shift in the phasetransition temperature of PNIPAM in PPL nanogelsi sa ttributed to the incorporation of PPL molecules to the network structures and an increase in the hydrophilicity of the polymer. After coating with BSA, the endotherm of PNIPAM shifts to the high-temperature regime.…”
Section: Resultsmentioning
confidence: 99%
“…More structures, such as rodlike structures, can be obtained by the self‐assembly approach. Our group described the synthesis and self‐assembly of bioconjugates composed of zwitterionic diblock copolymers with cleavable biotin and streptavidin ( Figure ) . A block copolymer of PEG and PDMAPS with cleavable biotin groups at the junction points (PEG‐ b ‐PDMAPSSSBiotin) was synthesized by a combination of click chemistry, thiol–disulfide exchange, and ATRP (Figure a).…”
Section: Synthesis Of Protein–nanoparticle Core–coronae Structuresmentioning
confidence: 99%
“…TEM images of self‐assembled structures of c) streptavidin‐bp 1.3 and d) streptavidin‐bp 2.9 in water at room temperature. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Synthesis Of Protein–nanoparticle Core–coronae Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research focused on preparing bioconjugates were mainly based on proteins such as bovine serum albumin (BSA), ovalbumin, chymotrypsin, streptavidin, and green fluorescent protein . Hoffman and co‐workers carried out pioneering work on preparation of various protein–PNIPAm conjugates for regulation of enzyme activity, triggered release, and enzyme recovery .…”
Section: Introductionmentioning
confidence: 99%